PERAN GENDER, PENDAPATAN DAN KESEJAHTERAAN SUBJEKTIF RUMAH TANGGA PETANI KOPI DI KECAMATAN SUMBEREJO KABUPATEN TANGGAMUS - Rama Ayu Fitri; Fembriarti Erry Prasmatiwi; Maya Riantini (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
This study aims to analyze gender roles, household income, subjective well-being and correlation between gender roles and subjective well-being of coffee farmer households in Sumberejo District, Tanggamus Regency.  This research is conducted by a survey method.  The location is chosen purposively in Sumbermulyo Village and Margoyoso Village, for the villages are the center of coffee production in Sumberejo District.  The samples in this research are 67 coffee farmers.  The samples determined by simple random sampling method.  Data were collected in March-April 2019 and analyzed by descriptive qualitative analysis, descriptive quantitative analysis and Chi-Square test.  The results of this research showed that gender roles in domestic activities and public activities were categorized as low and gender roles in social activities were categorized as moderate.  The average household income of coffee farmers was IDR39,467,773.88 per year.  The most contributed income was derived from coffee farming activities.  The subjective well-being was categorized as high. There was a significant relationship between gender roles and subjective well-being.Key words: coffee farming, gender roles, income, subjective well-being